Divided Counsel : The Anglo-American Response to Communist Victory in China - Martin, Edwin W. (Book collections on Project MUSE., 1986)
In the long controversy over the failure of the United States to extend early recognition to the People's Republic of China, the story of American efforts to maintain an official presence in the Communist-controlled areas of China until 1950 has been largely neglected. Moreover, the often bitter partisan strife over Sino-American relations during this period has obscured important facts or so distorted them that making an independent judgment is difficult indeed. In this book, Edwin Martin seeks to set the confused record straight by providing a well-documented, detailed account of American re.